Trends on Distance Education in the COVID-19: A Content Analysis Study - Ayfer Alper; Mutluhan Yılmaz; Ayşegül Pürbudak (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi, 2022)
It is clear that the world has changed with the latest pandemic known as the COVID-19. Moreover, a part of this change will be permanent. Because humanity has always been successful to create new alternatives during the crisis. When the COVID-19 pandemic was declared by World Health Organization (WHO) in March 2020, people worried about sustainable education as well as accessible health. Accessing and sustaining education were one of the main problems. This study is a content analysis. In this study, the re-searchers have investigated the educational sciences studies during the COVID-19 pan-demic. They have identified 61 relevant studies on Web of Science database and analysed them with the dimensions of research methods, data collection tools, working groups, sample size, parameters and findings/results. This examination has showed that most of these studies are quantitative studies. The most frequently used data collection tool is questionnaire. The most preferred working group are “university students” and “teachers”. The studies were conducted with groups between 1-101 and 101-200 individuals, at most respectively. The most compiled variables are “distance education” and “perception”. The most frequently reported points in the results are the limitations of distance education and the digital transition.